2019
DOI: 10.1155/2019/3210617
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Jordan: Prevalence, Awareness, Control, and Its Associated Factors

Abstract: Objectives. Determine the prevalence, awareness, and control rates of hypertension and their associated factors among Jordanian adults. Methods. A multistage sampling technique was used to select a nationally representative sample of adults from the population of Jordan. Trained interviewers collected data using a comprehensive structured questionnaire, measured anthropometric parameters, and collected blood samples. Results. This study included a total of 1193 men and 2863 women aged ranged from 18 to 90 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 18 publications
(27 reference statements)
12
58
3
Order By: Relevance
“…Table 1 shows that hypertensive patients who have cardiovascular complications are patients who have a history of not taking antihypertensive drugs. The results of this study are consistent with the results of the study of Yausef et al (2019) who found that only 30.7% of men and 35.1% of women who took antihypertensive drugs controlled their blood pressure. Inability to consume drugs of antihypertension has been a factor associated with the incidence of cardiovascular complications in patients with hypertension in this study.…”
Section: Methodssupporting
confidence: 92%
“…Table 1 shows that hypertensive patients who have cardiovascular complications are patients who have a history of not taking antihypertensive drugs. The results of this study are consistent with the results of the study of Yausef et al (2019) who found that only 30.7% of men and 35.1% of women who took antihypertensive drugs controlled their blood pressure. Inability to consume drugs of antihypertension has been a factor associated with the incidence of cardiovascular complications in patients with hypertension in this study.…”
Section: Methodssupporting
confidence: 92%
“…Additionally, a more aggressive strategy in the treatment of HTN (the use of combination antihypertensive agents) was common in most studies. On the contrary, the level of BP control in this study was higher than the results obtained from hospital-based studies conducted by Shelley et al in USA (49.8%), in six public primary care clinics of Malaysia (49.3%), 22 Al-Qahtani et al in Saudi Arabia (51.3%), Goverwa et al in Zimbabwe (32.8%), 42 Menanga et al in Cameroon (36.8%), 24 Khader et al among Jordanian adults (32.9%), 13 Mutua et al in Central Kenya (33.4%), 12 Animut et al at University of Gondar referral hospital, Ethiopia (50.4%). 16 Asgedom et al at Southwest Ethiopia (50.3%), 21 Teshome et al in Northwest Ethiopia (42.9%), 15 Lichisa et al in Adama, Ethiopia (43.6%), 43 Horsa et al in Ethiopia (26.2%), 9 Yazie et al in Ethiopia (30.1%) 2 and Gebremichael et al in Ethiopia (47.5%).…”
Section: Discussionmentioning
confidence: 64%
“…1,[5][6][7][8] It is one of the major, prevalent but modifiable risk factors, especially among patients with established cardiovascular disease (CVD) and cerebrovascular accidents. 2,9,10 As a result, HTN is the leading cause of morbidity and mortality among non-communicable diseases [11][12][13][14][15] and ranks third as a cause of disability-adjusted life-year causing about 7.1 million premature deaths each year. 11 Additionally, the complications of HTN account for 9.4 million deaths worldwide every year.…”
Section: Introductionmentioning
confidence: 99%
“…A multipurpose national household survey was conducted among Jordanian adults over a period of four months in the year 2017. The detailed study design, methods, and procedures were described in previous publications (4,5). In brief, a multistage sampling technique was used to select a nationally representative sample from the population of Jordan.…”
Section: Study Design and Samplingmentioning
confidence: 99%
“…In Jordan, the overall age-standardized prevalence rate of diabetes increased from 13.0% in 1994 to 23.7% in 2017 (4). In 2017, the agestandardized prevalence of hypertension in Jordan was 33.8% among men and 29.4% among women (5).…”
Section: Introductionmentioning
confidence: 99%